Conservation of the C5a peptidase genes in group A and B streptococci. - Chmouryguina, I (1996)
The chromosome of group B streptococci (GBS) contains a gene which is related to the C5a peptidase gene (scpA) of group A streptococci (GAS). scpA encodes a surface-associated peptidase (group A streptococcal C5a peptidase [SCPA]) which specifically cleaves C5a, a major chemoattractant generated in serum by activation of complement. The entire scpA-like gene (scpB) was cloned from a GBS strain and sequenced. The gene encodes an open reading frame of 3,450 bp, which corresponds to a deduced protein (SCPB) of 1,150 amino acids with a molecular weight of 126,237 Da. Nucleotide and deduced amino acid sequences of SCPB were found to be highly homologous to those of SCPAs from GAS. Unexpectedly, scpA12 is more similar to scpB than to another GAS gene, scpA49. The sequence 5' of the open reading frame, including transcription start and a termination site in the signal sequence, is also similar to that of scpA, although less conserved than the coding sequences. The near identity of GBS and GAS peptidases is consistent with horizontal transmission of the scp gene between these species. Recombinant SCPB was expressed in Escherichia coli by using the expression vector plasmid pGEX-4T-1 and was shown to be identical in size to the enzyme extracted from the parental GBS strain 78-471.